2022
DOI: 10.3389/fphar.2022.878776
|View full text |Cite
|
Sign up to set email alerts
|

Role of Licochalcone A in Potential Pharmacological Therapy: A Review

Abstract: Licochalcone A (LA), a useful and valuable flavonoid, is isolated from Glycyrrhiza uralensis Fisch. ex DC. and widely used clinically in traditional Chinese medicine. We systematically updated the latest information on the pharmacology of LA over the past decade from several authoritative internet databases, including Web of Science, Elsevier, Europe PMC, Wiley Online Library, and PubMed. A combination of keywords containing “Licochalcone A,” “Flavonoid,” and “Pharmacological Therapy” was used to help ensure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 113 publications
1
32
0
Order By: Relevance
“…Kaempferol suppresses proliferation, migration and invasion of fibroblast-like synoviocytes, and alleviates inflammation ( Yoon et al, 2013 ; Lee et al, 2018 ; Pan et al, 2018 ). Naringenin ( Hajizadeh et al, 2021 ; Wang et al, 2021 ), formononetin ( Machado Dutra et al, 2021 ), isorhamnetin ( Gong et al, 2020 ), and licochalcone A ( de Freitas et al, 2020 ; Li et al, 2022 ) have been reported to have antioxidant, anti-inflammatory, anti-cancer and osteogenic effects, showing great potential as agents for the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol suppresses proliferation, migration and invasion of fibroblast-like synoviocytes, and alleviates inflammation ( Yoon et al, 2013 ; Lee et al, 2018 ; Pan et al, 2018 ). Naringenin ( Hajizadeh et al, 2021 ; Wang et al, 2021 ), formononetin ( Machado Dutra et al, 2021 ), isorhamnetin ( Gong et al, 2020 ), and licochalcone A ( de Freitas et al, 2020 ; Li et al, 2022 ) have been reported to have antioxidant, anti-inflammatory, anti-cancer and osteogenic effects, showing great potential as agents for the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…The UV spectra of the chalcone compounds were recorded on a photodiode array UV−vis detector (SPD-M20A, 230 V, Shimadzu, Kyoto, Japan). 1 H NMR and 13 C NMR spectra of the chalcone derivatives were recorded on a Bruker AVANCE 500/125 MHz instrument using DMSO-d 6 or CDCl 3 as solvents. Solvent peaks appeared at 2.50 ppm (DMSO) and 7.28 ppm (CDCl 3 ) in the 1 H NMR spectrum and at 40.0 ppm (DMSO) and 77.0 ppm (CDCl 3 ) in the 13 C NMR spectrum.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Licochalcone A, a flavonoid isolated from the roots of Glycyrrhiza uralensis Fisch. ex DC., 1,2 has garnered significant attention in medicinal research in the past few decades. 1,3,4 Numerous studies have explored the pharmacological effects of licochalcone A, unveiling its potential as a therapeutic agent.…”
mentioning
confidence: 99%
See 2 more Smart Citations